The research project how to write it - Berry, Ralph 1931- (Routledge study guides, 2004)
Now in its fifth edition, this guide to project work continues to be an indispensable resource for all students undertaking research. Guiding the reader right through from preliminary stages to completion, The Research Project: How to write it sets out in clear and concise terms the main tasks involved in doing a research project, covering:* choosing a topic* using the library effectively* taking notes* shaping and composing the project* providing footnotes, documentation and a bibliography* avoiding common pitfalls. Fully updated throughout, this new edition features a chapter on making the most out of the Internet, from knowing where to start, to assessing the quality of the material found there. Other features include a model example of a well researched, clearly written paper with notes and bibliography and a chapter on getting published in a learned journal for more advanced researchers. Whether starting out or experienced in research, The Research Project: How to write it is an essential tool for success.